Acoustic Investigation of the Structure of Magneto-Rheological Fluid - Jozef Kudelcik; Peter Bury; Stefan Hardon; Michal Sedlacik; Tomas Plachy (Communications - Scientific letters of the University of Zilina, 2017)
The acoustic spectroscopy is used to study properties and changes in structural arrangement in silicone oil based magneto-rheological fluids with carbonyl iron particles upon the effect of an external magnetic field. Attenuation spectra at three temperatures for various concentrations of magnetic particles are presented. The attenuation of acoustic waves was measured for a jump change of the magnetic field to 200 mT as a function of the temperature. The relaxation effects for the acoustic attenuation after switching off the magnetic field and its decrease to the similar value as for clean silicone oil were observed. The change of acoustic attenuation in magneto-rheological fluid versus angle between the wave vector of acoustic waves and direction of the applied magnetic field was measured, too. For the anisotropy measurement are characteristic two local maxima from which results chain orientation in direction of the magnetic field.